Preparation method of nano ZnO-graphene composite material

By introducing modified nano zinc oxide and phthalate coupling agents into zinc oxide-graphene composite materials, and preparing nano ZnO-graphene composite materials by hydrothermal reaction and calcination treatment, the volume change and "aggregation" problems of composite materials during charge and discharge cycle are solved, and the structural stability and high-rate performance of the material are achieved.

CN119898812APending Publication Date: 2025-04-29GUANGZHOU SHUNZHUO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085445.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing zinc oxide-graphene composite materials are prone to volume expansion and contraction during the charge and discharge cycle, resulting in grain breakage, reducing the cycle life of the electrode, and are prone to "aggregation" during the despinning reaction, resulting in an initial irreversible capacity increase, and ultimately resulting in a capacity reduction.

Method used

A nano ZnO-graphene composite material is prepared using a method of preparing a nano ZnO-graphene composite material, including ultrasonic mixing of graphene oxide with modified nano zinc oxide, dispersant and phthalate coupling agent in an aqueous polyethylene glycol solution, and then conducting a hydrothermal reaction in a hydrothermal reactor, and obtaining the nano ZnO-graphene composite material by calcination treatment.

Benefits of technology

The nano ZnO-graphene composite material produced has stable structure, uniform particle size, high conductivity, excellent high rate performance and good cycle stability. It is suitable for zinc-based battery negative electrode materials and extends the cycle life of the electrode.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nano ZnO-graphene composite material preparation method, which comprises: S1, adding graphene oxide into a polyethylene glycol aqueous solution, and carrying out uniform ultrasonic mixing to obtain a graphene oxide suspension; s2, adding modified nano zinc oxide, a dispersing agent and a phthalate coupling agent into the graphene oxide suspension, performing ultrasonic dispersion, adding a precipitator, and performing mechanical stirring to obtain a mixed solution; s3, transferring the mixed solution into a hydrothermal reaction kettle, washing and drying; and S4, calcining the material obtained in the step S3. The nano ZnO-graphene composite material prepared by the method is stable in structure and uniform in granularity. The nano ZnO-graphene composite material prepared by the invention has high conductivity, super-excellent high rate performance and good cycle stability, is a very ideal zinc-based battery negative electrode material, and can be widely applied to the fields of various portable electronic equipment, electric automobiles, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite nanomaterials, and in particular to a method for preparing a nano ZnO-graphene composite material. Background Art

[0002] Composite materials prepared by different methods of metal compounds and graphene are mainly used in supercapacitors, batteries and other fields. Metal compounds include metal oxides, metal hydroxides, metal sulfides, etc. Among them, zinc oxide / graphene composite materials have the advantages of both zinc oxide and graphene. Zinc oxide has excellent electrical, optical and chemical properties, which makes it have application prospects in optoelectronics, solar cells, field emission, gas sensing and other fields. Graphene has good electrical, mechanical, optical and thermal properties. The ideal single-layer graphene has a large specific surface area (2630m 2 / g), is a very potential energy storage material. Graphene has good electrical conductivity, and the speed of its electrons reaches 1 / 300 of the speed of light, far exceeding the speed of electrons in general conductors.

[0003] However, when the existing zinc oxide-graphene composite material is used as the negative electrode of the battery, its volume is prone to expansion and contraction during the charge and discharge cycle, causing grain breakage, leading to electrode damage and reducing the cycle life of the electrode. In addition, it is easy to "agglomerate" during the de-insertion reaction, resulting in an increase in the initial irreversible capacity and ultimately a decrease in capacity. Summary of the invention

[0004] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a nano ZnO-graphene composite material, the preparation method comprising the following steps:

[0005] S1, adding graphene oxide to a polyethylene glycol aqueous solution, and mixing by ultrasonication to obtain a graphene oxide suspension;

[0006] S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, dispersing by ultrasonic, adding precipitant, and mechanically stirring to obtain a mixed solution;

[0007] S3, transferring the mixed solution to a hydrothermal reactor, washing and drying;

[0008] S4, calcining the material after step S3.

[0009] As a preferred technical solution, the preparation method specifically comprises the following steps:

[0010] S1, adding graphene oxide to a polyethylene glycol aqueous solution, and mixing by ultrasonication to obtain a graphene oxide suspension;

[0011] S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, ultrasonically dispersing for 0.5-1h, adding a precipitant, and mechanically stirring for 1-2h to obtain a mixed solution;

[0012] S3, transferring the mixed solution to a hydrothermal reactor, reacting at 150-400°C for 4-28h, washing with pure water and ethanol alternately for 2-4 times, and drying;

[0013] S4, calcining the material dried in step S3 at a temperature of 200-800° C., introducing an inert gas and calcining for 2-10 hours to obtain a nano ZnO-graphene composite material.

[0014] As a preferred technical solution, in step S1, the oxygen content of the graphene oxide is 30-40%.

[0015] As a preferred technical solution, the graphene oxide has a thickness of 0.55 to 1.2 nm and a diameter of 0.5 to 3 μm.

[0016] As a preferred technical solution, in step S1, the polyethylene glycol is at least one of PEG-200, PEG-400, PEG-600, PEG-800, and PEG-1000.

[0017] As a preferred technical solution, in step S1, the concentration of the graphene oxide suspension is 0.01-0.5 mg / ml.

[0018] As a preferred technical solution, in step S2, the modified nano zinc oxide is zinc oxide doped with aluminum oxide.

[0019] As a preferred technical solution, in the zinc oxide-doped aluminum oxide compound, the mass ratio of zinc oxide to aluminum oxide is 97-99%:3-1%.

[0020] As a preferred technical solution, the mass ratio of the graphene oxide to the modified nano zinc oxide is 1:5-10.

[0021] As a preferred technical solution, in step S2, the precipitant is at least one of ammonia water, ammonium carbonate and urea.

[0022] Beneficial Effects

[0023] 1. The nano ZnO-graphene composite material prepared by the present invention has a stable structure and uniform particle size.

[0024] 2. The nano ZnO-graphene composite material prepared by the present invention has high conductivity, super excellent high rate performance and good cycle stability. It is an ideal negative electrode material for zinc-based batteries and can be widely used in various portable electronic devices, electric vehicles, aerospace and other fields.

[0025] 3. The preparation method of the present invention has simple process, short reaction time, high yield, and is convenient for large-scale mass production. The prepared nano ZnO-graphene composite material has a uniform and stable structure.

[0026] 4. In the preparation method of the present invention, the use of phthalate coupling agent and dispersant can make the nano zinc oxide and graphene oxide disperse more evenly and solve the "agglomeration" problem; combined with other components in this system and the specific preparation method, the structure of the composite material is more stable, the damage to the electrode is reduced, and the cycle life is improved. DETAILED DESCRIPTION

[0027] The content of the present invention can be more easily understood by selecting the following detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definition in this specification shall prevail.

[0028] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a nano ZnO-graphene composite material, the preparation method comprising the following steps:

[0029] S1, adding graphene oxide to a polyethylene glycol aqueous solution, and uniformly mixing by ultrasonication to obtain a graphene oxide suspension, wherein the concentration of the graphene oxide suspension is 0.01 to 0.5 mg / ml; wherein the polyethylene glycol aqueous solution is prepared by mixing polyethylene glycol and water in a volume ratio of 1:1;

[0030] S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to graphene oxide suspension, ultrasonically dispersing for 0.5-1h, adding precipitant, and mechanically stirring for 1-2h to obtain a mixed solution; wherein, by mass volume ratio, graphene oxide: modified nano zinc oxide: dispersant: phthalate coupling agent: precipitant = 1mg: 5-10mg: 0.5-1ml: 0.1-0.5ml: 0.1-0.5mg;

[0031] S3, transferring the mixed solution to a hydrothermal reactor, reacting at 150-400°C for 4-28h, washing with pure water and ethanol alternately for 2-4 times, and drying;

[0032] S4, calcining the material dried in step S3 at a temperature of 200-800° C., introducing an inert gas and calcining for 2-10 hours to obtain a nano ZnO-graphene composite material.

[0033] In some preferred embodiments, in step S1, the oxygen content of the graphene oxide is 30-40%.

[0034] In some preferred embodiments, the graphene oxide has a thickness of 0.55 to 1.2 nm and a diameter of 0.5 to 3 μm.

[0035] In some preferred embodiments, in step S1, the polyethylene glycol is at least one of PEG-200, PEG-400, PEG-600, PEG-800, and PEG-1000.

[0036] In some preferred embodiments, in step S2, the modified nano zinc oxide is zinc oxide doped with aluminum oxide.

[0037] In some preferred embodiments, in the zinc oxide-doped aluminum oxide compound, the mass ratio of zinc oxide to aluminum oxide is 97-99%:3-1%.

[0038] In some preferred embodiments, in the zinc oxide-doped aluminum oxide compound, the mass ratio of zinc oxide to aluminum oxide is 99%:1%.

[0039] In some preferred embodiments, the dispersant is one of Keying dispersant KYC-913, Keying dispersant KYC-9166, and Keying dispersant KYC-926.

[0040] In some preferred embodiments, the dispersant is Keying dispersant KYC-913.

[0041] In some preferred embodiments, the phthalate coupling agent is at least one of isopropyl tris(dioctyl pyrophosphate)phthalate, isopropyl tris(dioctyl phosphate)phthalate, isopropyl dioleyloxy(dioctyl phosphate)phthalate, monoalkoxy unsaturated fatty acid phthalate, and bis(dioctyl pyrophosphate)ethylene phthalate.

[0042] In some preferred embodiments, in step S2, the precipitant is at least one of ammonia water, ammonium carbonate and urea.

[0043] Example

[0044] The technical scheme of the present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the examples. Unless otherwise specified, the raw materials in the present invention are all commercially available.

[0045] Example 1

[0046] Embodiment 1 provides a method for preparing a nano ZnO-graphene composite material, the preparation method comprising the following steps:

[0047] S1, adding graphene oxide to a polyethylene glycol aqueous solution, and uniformly mixing by ultrasonication to obtain a graphene oxide suspension, wherein the concentration of the graphene oxide suspension is 0.01 mg / ml; wherein the polyethylene glycol aqueous solution is prepared by mixing polyethylene glycol and water in a volume ratio of 1:1, and the polyethylene glycol is PEG-200;

[0048] S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, ultrasonically dispersing for 0.5 h, adding a precipitant, and mechanically stirring for 1 h to obtain a mixed solution; wherein, by mass volume ratio, graphene oxide: modified nano zinc oxide: dispersant: phthalate coupling agent: precipitant = 1 mg: 5 mg: 0.5 ml: 0.1 ml: 0.1 mg;

[0049] S3, transferring the mixed solution to a hydrothermal reactor, reacting at 150°C for 28h, washing twice with pure water and ethanol alternately, and drying;

[0050] S4, calcining the material dried in step S3 at 200° C. for 10 hours under nitrogen to obtain a nano ZnO-graphene composite material.

[0051] In step S1, the oxygen content of the graphene oxide is 30-40%, the thickness of the graphene oxide is 0.55-1.2 nm, and the diameter is 0.5-3 μm (Beijing Dekedaojin Technology Co., Ltd.).

[0052] In step S2, the modified nano zinc oxide is zinc oxide doped with aluminum oxide, wherein the mass ratio of zinc oxide to aluminum oxide is 99%:1% (Beijing Dekedaojin Technology Co., Ltd., model: DK444).

[0053] In step S2, the dispersant is Keying dispersant KYC-926.

[0054] In step S2, the phthalate coupling agent is isopropyl tri(dioctyl pyrophosphate)phthalate.

[0055] In step S2, the precipitant is aqueous ammonia.

[0056] This example also provides a nano ZnO-graphene composite material obtained by the above preparation method.

[0057] Example 2

[0058] Embodiment 2 provides a method for preparing a nano ZnO-graphene composite material, the preparation method comprising the following steps:

[0059] S1, adding graphene oxide to a polyethylene glycol aqueous solution, and uniformly mixing by ultrasonication to obtain a graphene oxide suspension, wherein the concentration of the graphene oxide suspension is 0.5 mg / ml; wherein the polyethylene glycol aqueous solution is prepared by mixing polyethylene glycol and water in a volume ratio of 1:1; and the polyethylene glycol is PEG-400.

[0060] S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, ultrasonically dispersing for 1 hour, adding a precipitant, and mechanically stirring for 2 hours to obtain a mixed solution; wherein, by mass volume ratio, graphene oxide: modified nano zinc oxide: dispersant: phthalate coupling agent: precipitant = 1 mg: 10 mg: 1 ml: 0.5 ml: 0.5 mg;

[0061] S3, transferring the mixed solution to a hydrothermal reactor, reacting at 400°C for 4 hours, washing with pure water and ethanol alternately for 4 times, and drying;

[0062] S4, calcining the material dried in step S3 at 800° C. for 2 h under argon gas to obtain a nano ZnO-graphene composite material.

[0063] In step S1, the oxygen content of the graphene oxide is 30-40%, the thickness of the graphene oxide is 0.55-1.2 nm, and the diameter is 0.5-3 μm (Beijing Dekedaojin Technology Co., Ltd.).

[0064] In step S2, the modified nano zinc oxide is zinc oxide doped with aluminum oxide, wherein the mass ratio of zinc oxide to aluminum oxide is 99%:1% (Beijing Dekedaojin Technology Co., Ltd., model: DK444).

[0065] In step S2, the dispersant is Keying dispersant KYC-9166.

[0066] In step S2, the phthalate coupling agent is isopropyl tri(dioctylphosphoyl)phthalate.

[0067] In step S2, the precipitant is ammonium carbonate.

[0068] This example also provides a nano ZnO-graphene composite material obtained by the above preparation method.

[0069] Example 3

[0070] Embodiment 3 provides a method for preparing a nano ZnO-graphene composite material, the preparation method comprising the following steps:

[0071] S1, adding graphene oxide to a polyethylene glycol aqueous solution, and uniformly mixing by ultrasonication to obtain a graphene oxide suspension, wherein the concentration of the graphene oxide suspension is 0.3 mg / ml; wherein the polyethylene glycol aqueous solution is prepared by mixing polyethylene glycol and water in a volume ratio of 1:1; and the polyethylene glycol is PEG-600.

[0072] S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, ultrasonically dispersing for 45 minutes, adding a precipitant, and mechanically stirring for 1.5 hours to obtain a mixed solution; wherein, by mass volume ratio, graphene oxide: modified nano zinc oxide: dispersant: phthalate coupling agent: precipitant = 1mg: 8mg: 0.8ml: 0.3ml: 0.3mg;

[0073] S3, transferring the mixed solution to a hydrothermal reactor, reacting at 250°C for 18 hours, washing with pure water and ethanol alternately for 3 times, and drying;

[0074] S4, calcining the material dried in step S3 at 500° C. for 6 hours under nitrogen flow, to obtain a nano ZnO-graphene composite material.

[0075] In step S1, the oxygen content of the graphene oxide is 30-40%, the thickness of the graphene oxide is 0.55-1.2 nm, and the diameter is 0.5-3 μm (Beijing Dekedaojin Technology Co., Ltd.).

[0076] In step S2, the modified nano zinc oxide is zinc oxide doped with aluminum oxide, wherein the mass ratio of zinc oxide to aluminum oxide is 99%:1% (Beijing Dekedaojin Technology Co., Ltd., model: DK444).

[0077] In step S2, the dispersant is Keying dispersant KYC-913.

[0078] In step S2, the phthalate coupling agent is a monoalkoxy unsaturated fatty acid phthalate.

[0079] In step S2, the precipitant is urea.

[0080] This example also provides a nano ZnO-graphene composite material obtained by the above preparation method.

[0081] Comparative Example 1

[0082] The concentration of the graphene oxide suspension in step 1 was changed to 1 mg / ml, and the rest was the same as in Example 3.

[0083] Comparative Example 2

[0084] The concentration of the graphene oxide suspension in step 1 was changed to 5 mg / ml, and the rest was the same as in Example 3.

[0085] Comparative Example 3

[0086] The mass ratio of graphene oxide to modified nano zinc oxide was changed to 1:1, and the rest was the same as in Example 3.

[0087] Comparative Example 4

[0088] The mass ratio of graphene oxide to modified nano zinc oxide was changed to 1:50, and the rest was the same as in Example 3.

[0089] Comparative Example 5

[0090] The modified nano zinc oxide was replaced with ordinary nano zinc oxide (Beijing Dekedaojin Technology Co., Ltd., model: DK-ZnO-30), and the rest was the same as in Example 3.

[0091] Performance Testing

[0092] 1. Preparation of 2430 type battery: The nano ZnO-graphene composite material obtained in Examples 1 to 3 and Comparative Examples 1 to 5, N-methylpyrrolidone containing 6 to 7% polyvinylidene fluoride and 2% conductive carbon black are mixed evenly and coated on copper foil. The coated pole piece is placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours for standby use. The simulated battery is assembled in a German Braun glove box filled with argon gas. The electrolyte is 1M LiPF6+EC:EMC:DMC=1:1:1 (volume ratio). The metal lithium sheet is the counter electrode. The electrochemical performance test is carried out on an American ArbinBT2000 battery tester. The charge and discharge system is: the potential is limited to 0-1.5V for charge / discharge test, that is, the battery is charged with a charging current of 0.5mA / cm2 while maintaining a voltage of 0.01V, and then the charging current is 0.02mA / cm2 while maintaining a voltage of 0.01V to continue charging. The battery was discharged with a discharge current of 0.5 mA / cm2 until the voltage reached 1.5 V. The test results are shown in Table 1.

[0093] Table 1

[0094] Example First discharge capacity / mAh / g Capacity retention rate after 500 cycles % Example 1 >600 92 Example 2 >600 91 Example 3 >600 94 Comparative Example 1 <400 76 Comparative Example 2 <400 74 Comparative Example 3 <400 79 Comparative Example 4 <400 69 Comparative Example 5 <400 65

[0095] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a nano ZnO-graphene composite material, characterized in that: The preparation method comprises the following steps: S1, adding graphene oxide to a polyethylene glycol aqueous solution, and mixing by ultrasonication to obtain a graphene oxide suspension; S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, dispersing by ultrasonic, adding precipitant, and mechanically stirring to obtain a mixed solution; S3, transferring the mixed solution to a hydrothermal reactor, washing and drying; S4, calcining the material after step S3.

2. The method for preparing the nano ZnO-graphene composite material according to claim 1, characterized in that: The preparation method specifically comprises the following steps: S1, adding graphene oxide to a polyethylene glycol aqueous solution, and mixing by ultrasonication to obtain a graphene oxide suspension; S2, adding modified nano zinc oxide, dispersant, and phthalate coupling agent to the graphene oxide suspension, ultrasonically dispersing for 0.5-1h, adding a precipitant, and mechanically stirring for 1-2h to obtain a mixed solution; S3, transferring the mixed solution to a hydrothermal reactor, reacting at 150-400°C for 4-28h, washing with pure water and ethanol alternately for 2-4 times, and drying; S4, calcining the material dried in step S3 at a temperature of 200-800° C., introducing an inert gas and calcining for 2-10 hours to obtain a nano ZnO-graphene composite material.

3. The method for preparing the nano ZnO-graphene composite material according to claim 1 or 2, characterized in that: In step S1, the oxygen content of the graphene oxide is 30-40%.

4. The method for preparing the nano ZnO-graphene composite material according to claim 3, characterized in that: The graphene oxide has a thickness of 0.55 to 1.2 nm and a diameter of 0.5 to 3 μm.

5. The method for preparing the nano ZnO-graphene composite material according to claim 1 or 2, characterized in that: In step S1, the polyethylene glycol is at least one of PEG-200, PEG-400, PEG-600, PEG-800, and PEG-1000.

6. The method for preparing the nano ZnO-graphene composite material according to claim 1 or 2, characterized in that: In step S1, the concentration of the graphene oxide suspension is 0.01-0.5 mg / ml.

7. The method for preparing the nano ZnO-graphene composite material according to claim 1 or 2, characterized in that: In step S2, the modified nano zinc oxide is zinc oxide doped with aluminum oxide.

8. The method for preparing the nano ZnO-graphene composite material according to claim 7, characterized in that: In the zinc oxide doped aluminum oxide compound, the mass ratio of zinc oxide to aluminum oxide is 97-99%:3-1%.

9. The method for preparing the nano ZnO-graphene composite material according to claim 1 or 2, characterized in that: The mass ratio of the graphene oxide to the modified nano zinc oxide is 1:5-10.

10. The method for preparing the nano ZnO-graphene composite material according to claim 1 or 2, characterized in that: In step S2, the precipitant is at least one of ammonia water, ammonium carbonate and urea.